The influence of thermal tempering on the fracture resistance, surface microstructure, elemental surface composition, and phase analysis of four heat-pressed lithia-based glass ceramic crowns - Khaled Nasser; Amr EL-Etreby; Soha Osama Nabih (BMC Oral Health)
Abstract Background This in-vitro study aimed to evaluate the impact of thermal tempering and ceramic type on the fracture resistance, surface microstructure, elemental surface composition and phase analysis of four heat-pressed glass ceramics. Methods A total of 84 glass-ceramic crowns were pressed and randomly allocated into four equal groups (n = 21) according to the ceramic type: Group (E): IPS e.max Press, Group (L): GC initial LiSi Press, Group (C): Celtra Press and Group (A): VITA Ambria. The crowns of each group were equally allocated into three subgroups (n = 7) regarding the subsequent thermal tempering temperature. Subgroup (T0): No tempering. Subgroup (T1): Tempering at 9% below pressing temperature. Subgroup (T2): Tempering at 5% below pressing temperature. Samples were tested for fracture resistance using a universal testing machine. A scanning electron microscope, X-ray diffraction, and Energy Dispersive x-ray analysis were utilized to disclose the microstructural features. Results When there is no tempering, IPS e.max press showed a significant elevated fracture resistance (P-value = 0.002). There was an insignificant difference between other ceramics. While with tempering (T2) as well as (T1), Lisi press (L) showed a significant elevated fracture resistance. There was an insignificant difference between other ceramics (P-value = 0.004). Conclusions Incorporation of zirconia oxide into the lithium disilicate glass matrix did not show improvement in the fracture resistance. Thermal tempering procedure had significant effect on fracture resistance. Thermal tempering technique had no influence the elemental surface composition and phase analysis yet T2 samples showed changes in crystal size and orientation.